A descriptive analysis of anglicisms used in ecuadorian magazines - Yepez Rios, Nelly Patricia (2011)
This study aims to identify and analyze the use of anglicisms in Ecuadorian magazines, taking as variables the scholarly, cultural and general interest magazines. Examples of words which come from the English language are provided to illustrate how this language has influenced the Spanish written and to help the readers to understand the morphological, semantic and syntactic approaches of those anglicisms as well as the possible causes for their introduction into the Spanish language. The research was conducted in Quito- Ecuador; the magazines analyzed were : El Búho and El Apuntador for the Cultural variable; Ecuador Terra Incógnita and Capital for the Scholarly variable and Cosas and Diners magazines for the General Interest variable. This study was addressed using a qualitative and quantitative approach. Each magazine was carefully analyzed by using skimming and scanning, reading techniques and note taking in order to collect data about the anglicisms used in Spanish magazines. This research evidences that wõthere is a bigger amount of anglicisms in general interest magazines, a forty percent as opposed to the nineteen percent of English terms found in scholarly magazines which aim to convey a more formal language due to the audiences they approach.